A highly sensitive ratiometric fluorescent probe based on fluorescein coumarin for detecting hydrazine in actual water and biological samples. Issue 2 (10th January 2023) - Lv, Linlin; Luo, Weiwei; Zhou, Yixiao; Li, Tiechun; Diao, Quanping; Ma, Pinyi; Song, Daqian
Abstract: Hydrazine (N2 H4 ) is a highly toxic and harmful chemical reagent. Fluorescent probes are simple and efficient tools for sensitive monitoring of N2 H4 enrichment in the environment, humans, animals, and plants. In this work, a ratiometric fluorescent probe (FP‐1) containing coumarin was used for hydrazine detection. The proposed FP‐1 probe had a linear detection range of 0–250 μM and a limit of detection (LOD) of 0.059 μM (1.89 ppb). A large red Stokes shift was observed in fluorescence and UV–vis absorption spectra due to the hydrolysis of ester bonds between FP‐1 and hydrazine. The hydrazine detection mechanism of FP‐1 was also investigated using density functional theory (DFT) calculations. Finally, FP‐1 could sensitively and selectively monitor hydrazine in actual water samples and BEAS‐2B cells. Therefore, it has great application potential in environmental monitoring and disease diagnosis. Abstract : We have designed and synthesized a novel ratiometric fluorescent probe FP‐1 for distinguishing detection hydrazine in aqueous solution. FP‐1 was successfully applied in detection of actual water samples and human normal lung epithelial cells imaging.